Legal Aspects of Hospital Waste Management based on Law Number 17 of 2023 Concerning Health - Br.Sembiring, Tamaulina; Pratiwi, Septi Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The abstract of this article discusses medical waste management in Indonesian hospitals with a focus on the implementation of related regulations and regulations, especially after the enactment of Law Number 17 of 2023 concerning Health. Medical waste, which contains potential dangers to the environment and public health, is a major concern in the context of safe and standardized management. This article uses a normative legal approach to analyze the laws and regulations governing medical waste management in hospitals. The research results show that even though there are regulations such as the Republic of Indonesia Minister of Health Regulation no. 18 of 2020, its implementation still faces challenges such as low compliance with procedures, lack of effective socialization, and the need for training for health workers. The recommendations put forward include increasing outreach, training health workers, using technology in medical waste management, regular audits, inter-agency cooperation, strict implementation of laws, as well as further research to increase the effectiveness of medical waste management. It is hoped that this article can contribute to efforts to improve medical waste management in Indonesian hospitals in order to better protect the environment and public health.